1993
DOI: 10.1111/j.1748-1716.1993.tb09623.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic contractions of isolated small arteries from rat: role of calcium

Abstract: In order to investigate the mechanisms behind rhythmic contractions in small arteries of the mesenteric arcade from Wistar rats, the calcium dependency of the oscillations in response to noradrenaline activation was tested on isolated vessels. Application of 1 microM ryanodine or 30 microM TMB-8 (procedures known to inhibit Ca2+ release from intracellular stores) totally abolished the rhythmic activity, even though the antagonists had opposite effects on the amplitude of the contractile response to noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
5
39
0
Order By: Relevance
“…This has been demonstrated previously 5,6 and is confirmed in the present study. Also, the oscillations of [Ca 2ϩ ] i and tension were always prevented by inhibitors of the SR function (Table).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This has been demonstrated previously 5,6 and is confirmed in the present study. Also, the oscillations of [Ca 2ϩ ] i and tension were always prevented by inhibitors of the SR function (Table).…”
Section: Resultssupporting
confidence: 81%
“…1,2 Vasomotion is known to be associated with slow oscillations of smooth muscle membrane potential 3 and of intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ). 4 It has also been demonstrated that the function of the sarcoplasmic reticulum (SR) is critically important for the activity, 5,6 whereas potassium channels play only a modulatory role. 7,8 The role of the endothelium differs between vascular beds.…”
mentioning
confidence: 99%
“…Some previous models of vasomotion have assumed that oscillations are intrinsic to the intracellular dynamics of smooth muscle activation (Achakri et al, 1994;Gonzalez-Fernandez & Ermentrout, 1994;Parthimos et al, 1999Parthimos et al, , 2007Peng et al, 2001;Gustafsson & Nilsson, 1993b). In the present model, the dynamics of activation are governed by a simple first-order differential equation that has no intrinsic oscillatory behaviour.…”
Section: Discussionmentioning
confidence: 90%
“…Studies on RC have been undertaken for more than 150 years [10][11][12][13] , after the first report by Jones regarding the veins of bats' wings in 1852 [11] . To date, the mechanism of RC is still not very clear, and plenty of cellular components of the vascular smooth muscle cell have been reported to participate in generating RC; these include RyR and the Ca 2+ -pump of SR, the L-type Ca 2+ channel, the K + channel, Na + , K + -ATPase and the nitric oxide (NO)-cGMP system.…”
Section: Introductionmentioning
confidence: 99%